A system for inducing concurrent tactile and nociceptive sensations at the same site using electrocutaneous stimulation - Steenbergen, Peter; Trojan, Jörg; Flor, Herta (Behavior research methods, 2012)
Studies of the interaction between mechanoception and nociception would benefit from a method for stimulation of both modalities at the same location. For this purpose, we developed an electrical stimulation device. Using two different electrode geometries, discs and needles, the device is capable of inducing two distinct stimulus qualities, dull and sharp, at the same site on hairy skin. The perceived strength of the stimuli can be varied by applying stimulus pulse trains of different lengths. We assessed the perceived stimulus qualities and intensities of the two electrode geometries at two levels of physical stimulus intensity. In a first series of experiments, ten subjects participated in two experimental sessions. The subjects reported the perceived quality and intensity of four different stimulus classes on visual analogue scales (VASs). In a second series, we added a procedure in which subjects assigned descriptive labels to the stimuli. We assessed the reproducibility of the VAS scores by calculating intraclass correlation coefficients. The results showed that subjects perceived stimuli delivered through the disc electrodes as dull and those delivered through the needles as sharp. Increasing the pulse train length increased the perceived stimulus intensities without decreasing the difference in quality between the electrode types. The intraclass correlation coefficients for the VAS scores ranged from .75 to .95. The labels that were assigned for the two electrode geometries corresponded to the descriptors for nociception and touch reported by other researchers. We concluded that our device is capable of reliably inducing tactile and nociceptive sensations of controllable intensity at the same skin site.